Anti-Malarial Activity of Goniothalamus Scortechinii King - Md Yusuf, Noor Azian (2006)
Malaria remains the most devastating infectious parasitic disease, inflicting both death and economic loses on at least half the world population. Numerous attempts have been made to control the disease by using vector control measures or/and chemoprophylaxis, but they have had limited success. Immunoprophylaxis hold promises but effective vaccines are still not available. Presently, the most effective way of dealing with malaria is the administration of chemotherapeutic agents. Although drugs treatments of malaria are currently the best means of disease management, there is an urgent need for the development of effective anti-malarial drugs. Earlier assessment of Goniothalamus scortechinii King showed to possess significant anti-malarial properties, in vitro. A phytochemical study of G. schortechinii King was thus carried out and has led to the isolation and characterization of two compounds, goniothalamin and pinocembrine, from the bioactive chloroform fraction. Both compounds were assayed for anti-malarial activity using the pLDH method. Both exhibited anti-malarial activity against P. falciparum in different degrees, goniothalamin gave an IC50 value of 4.0824 μg/ml while pinocembrine gave 19.308 μg/ml. Goniothalamin was evaluated for its anti-malaria activity in-vivo using 4-Day Suppressive Test against Plasmodium berghei ANKA strain in Swiss Albino Mice. The 4DT was carried out by inoculating the clean mice with P berghei ANKA strain and the infected mice were then treated orally and subcutaneously with goniothalamin. The suppression of parasite parasitemia and the ED90 value of goniothalamin were determined. Control drug used in this study was Chloroquine. Results showed that goniothalamin when given orally at a dose of 90 and 120 mg/kg mice body weight, exhibited suppressions of P. berghei infection of 98% and 99.7%, respectively. Meanwhile, goniothalamin given subcutaneously at a dose 120 mg/kg mice body weight gave 90.5% suppression of P. berghei infection. Ex vivo assay was carried out to investigate the effect of goniothalamin towards P. falciparum in vitro using the mouse serum treated with goniothalamin. This was done to prove that goniothalamin reaction toward P. falciparum should same as reaction towards P. berghei in in vivo reaction. Ex vivo test was carried out using pLDH assay with serum of mice given goniothalamin orally and subcutaneously. A graph to determine the 90% inhibition of drugs-serum towards P. falciparum was plotted for each treated mice serum. Results showed the IS90 of mice serum given goniothalamin orally was ranging from 0.050 to 4.00 μg/ml, for subcutaneous route the IS90 was ranging from 0.009-4.750 μg/ml. A graph for estimating the length of time goniothalamin can remain in the blood was plotted. This gave the estimated time of goniothalamin both given orally and subcutaneously can remained a minimum of 6 hours in the blood. In conclusion, goniothalamin does strongly inhibit P. falciparum, although it is not as potent as the standard drugs in use. More investigations such as drug combination, cytotoxicity, mechanism of action and toxicology studies, need to be carried out in order to determine its full potential as an anti-malarial.